The last phase of life with dementia in Swiss nursing homes: the study protocol of the longitudinal and prospective ZULIDAD study. Issue 1 (December 2016) - Eicher, Stefanie; Theill, Nathan; Geschwindner, Heike; Moor, Caroline; Wettstein, Albert; Bieri-Brüning, Gabriela; Hock, Christoph; Martin, Mike; Wolf, Henrike; Riese, Florian
Abstract Background The proportion of older people with advanced dementia who will die in nursing homes is constantly growing. However, little is known about the dying phase, the type of symptoms, the management of symptoms and the quality of life and dying in people with advanced dementia. The ZULIDAD (Zurich Life and Death with Advanced Dementia) study aims at extending the current scientific knowledge by providing first data from Switzerland. Methods The ZULIDAD study employs a prospective design to study nursing home residents with advanced dementia for three years or until their death in eleven nursing homes in Zurich. Observational data from quarterly questionnaires for relatives and primary nurses is combined with data from the Resident Assessment Instrument – Minimum Data Set (RAI-MDS). Special focus is put on 1) the cross-sectional analysis of baseline and post-mortem data regarding quality of life and quality of dying and how the perceptions of these measures differ between relatives and primary nurses, 2) the longitudinal analyses of established health outcome measures (e.g., EOLD, MSSE, BISAD, QUALID) in order to understand their trajectories and 3) international comparisons of cross-sectional and longitudinal data. Discussion The ZULIDAD study is one of the few existing prospective studies on end-of-life care in dementia and it is the first prospective study to describe the situation in Switzerland. Its multi-perspective approach allows a comprehensive approximation to central health outcome measures at the end of life such as pain, suffering or quality of life. Providing insights into the current provision of care, it can serve as a basis for improving dementia end-of-life care in Switzerland and internationally.